US-India Strategic Bargaining and Power Balancing in South Asia - Manzoor Ahmad; Naveeda Yousaf; Zahir Shah (Journal of Political Studies, 2016)
The relationship between United States and India has transformed from estrangement to wider engagement since 2004. With the convergence of interests and shared values both the US and India came close towards each other and evolved strategic partnership through civil nuclear cooperation. This paper analyze the cost and benefit of strategic partnership with India for US, the impact of India’s emergence as regional power on South Asian balance of power and its impact on Pak-US relationship. It also focuses on security structure of the region and challenges for the US to maintain strategic partnership with two rival states (India and Pakistan). The paper also gives some recommendations for balancing power in the region in order to ensure durable peace not only between India and Pakistan but also in south Asia.